Reframing Assessment Concepts - Taylor, Catherine S.; Nolen, Susan Bobbitt (Education Policy Analysis Archives, 1996)
We question the utility of traditional conceptualizations of validity and reliability, developed in the context of large scale, external testing, and the psychology of individual differences, for the context of the classroom. We compare traditional views of validity and reliability to alternate frameworks that situate these constructs in teachers' work in classrooms. We describe how we used these frameworks to design an assessment course for preservice teachers, and present data that suggest students in the redesigned course not only saw the course as more valuable in their work as teachers, but developed deeper understandings of validity and reliability than did their counterparts in a traditional tests and measurement course. We close by discussing the implications of these data for the teaching of assessment, and for the use and interpretation of classroom assessment data for purposes of local and state accountability.